Synthesis, Spectroscopic and Antimicrobial Studies on Copper(II), Cobalt(II), Nickel(II) and Manganese(II) Complexes of N-(2-Ethylphenyl) N'-Picolinoyl Hydrazine - Pal Singh, Netra; Singh, Jagvir (Asian Journal of Chemistry, 2012)
Novel ligand N-(2-ethylphenyl)N'-picolinoyl hydrazine (L) has been synthesized from pyridine-2-acetyl chloride and N-(2-ethylphenyl) hydrazine by condensation in ethanol. The ligand and its Cu(II), Co(II), Ni(II) and Mn(II) complexes have been characterized by microanalysis, magnetic susceptibility, FT-IR, 1H and 13C NMR, mass spectrum and UV-visible spectroscopy techniques. It is suggested that two ligands coordinate to the metal ion by hydrazine nitrogen atoms and pyridine nitrogen atoms to form square-planar geometry of [Cu(L)2]Cl2 but the complexes of cobalt(II), nickel(II) and manganese(II) have octahedral geometry. Newly synthesized ligand and its metal complexes have been screened against S. aureus (ATCC 25923), S. aureus (ATCC 3160) bacterial species and C. albicans (227) and S. cereviscae (361) fungal species.